“Flow Reversal” and Cure in a Case of Giant Intracranial Aneurysm: A Case Report - Shah, Abhidha; Vutha, Ravikiran; Doshi, Jash; Trivedi, Nishit; Goel, Atul (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
We describe the case of an 11-year-old girl having a giant anterior circulation aneurysm. The ipsilateral internal carotid artery was entirely blocked and the aneurysm was supplied by posterior circulation. Following a high-flow bypass that connected the external carotid artery to the middle cerebral artery, the giant aneurysm thrombosed spontaneously. We discuss several relatively rare and unique features of the case.
Keywords: giant aneurysm; flow diversion; internal carotid artery; high-flow bypass